Novel multi-responsive P2VP-block-PNIPAAm block copolymers via nitroxide-mediated radical polymerization - Cathrin Corten; Katja Kretschmer; Dirk Kuckling (Beilstein Journal of Organic Chemistry, 2010)
Linear soluble multi-responsive block copolymers are able to form so called schizophrenic micelles in aqueous solution. Here, such polymers are prepared via nitroxide-mediated radical polymerization (NMRP). In a first step nitroxide-terminated poly(2-vinylpyridine) (P2VP) was prepared with different molecular weights and narrow molecular weight distributions. The best reaction conditions, optimized by kinetic studies, were bulk polymerization at 110 °C. Using P2VP as a macroinitiator, the synthesis of new soluble linear block copolymers of P2VP and poly(N-isopropylacrylamide) (PNIPAAm) (P2VP-block-PNIPAAm) was possible. The nitroxide terminated polymers were characterized by nuclear magnetic resonance (NMR) spectroscopy, size exclusion chromatography (SEC) and matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Thermal properties were investigated by the differential scanning calorimetry (DSC). Block copolymers showed pH- and temperature-responsive solubility in aqueous media. By increasing the P2VP content, the phase transition temperature shifted to lower temperatures (e.g. 26 °C for P2VP114-block-PNIPAAm180). Depending on the resulting block length, temperature and pH value of aqueous solution, the block copolymers form so called schizophrenic micelles. The hydrodynamic radius Rh of these micelles associated with pH values and temperature was analyzed by dynamic light scattering (DLS). Such kind of block copolymers has potential for many applications, such as controlled drug delivery systems.